2020
DOI: 10.3233/jad-191125
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar White Matter Disruption in Alzheimer’s Disease Patients: A Diffusion Tensor Imaging Study

Abstract: Telephone number: +44(0) 1273 873509; Fax number: +44 (0) 1273 876721; E mail address: m.bozzali@bsms.ac.uk Abstract The cognitive role of the cerebellum has recently gained much attention, and its pivotal role in Alzheimer's disease (AD) has now been widely recognized. Diffusion Tensor Imaging (DTI) has been used to evaluate the disruption of the microstructural milieu in AD, and though several white matter (WM) tracts such as corpus callosum, inferior and superior longitudinal fasciculus, cingulum, fornix an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…An increasing number of imaging studies have confirmed that cerebellar Crus II and lobular IX are associated with cognitive networks (32,34,35), particularly with the default mode network (DMN) and fronto-parietal network (FPN) (36)(37)(38). The anterior cerebellum and lobule VIII are associated with movement, whereas the posterior cerebellum (i.e., lobule VI-Crus I, lobule Crus II-VIIB, and lobule IX) are critical for cognitive representation (39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of imaging studies have confirmed that cerebellar Crus II and lobular IX are associated with cognitive networks (32,34,35), particularly with the default mode network (DMN) and fronto-parietal network (FPN) (36)(37)(38). The anterior cerebellum and lobule VIII are associated with movement, whereas the posterior cerebellum (i.e., lobule VI-Crus I, lobule Crus II-VIIB, and lobule IX) are critical for cognitive representation (39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of CCD include the involvement of cortico-pontocerebellar and the cerebello-thalamo-cortical circuits (Dum and Strick, 2003;Di Lorenzo et al, 2013). Using diffuse tension imaging (DTI), Sofia Toniolo et al provide the evidence of the impairment of microstructural fiber integrity of cerebellum WM tracts in AD (Toniolo et al, 2020). However, whether the focal change in the cerebellum is a form of Wallerian degeneration or the result of accumulation of AD pathological substrates in the cerebellum itself is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Disease-specific clusters of cerebellar atrophy have been found in Alzheimer’s disease, Frontotemporal Dementia and Amyotrophic lateral sclerosis 78 . Functional connectivity alterations 22,23 and white matter disruption 79 characterize cerebro-cerebellar loops in Alzheimer’s disease patients. Abnormal network connectivity between cerebellum and cerebral cortical regions has been confirmed in the main subtypes of Frontotemporal Dementia 80,81 (behavioral-variant, semantic dementia and progressive nonfluent aphasia).…”
Section: Discussionmentioning
confidence: 99%